Gene locus polymorphisms and expression levels of interleukin-1 in lumbar disc disease: A MOOSE-compliant meta-analysis and immunohistochemical study. Issue 43 (28th October 2022) - Yang, Kunxue; Xiao, Qianyi; Zhang, Ruijun; Meng, Dihua; Wang, Jiaqi; Wei, Qingjun; Jiang, Hua
Abstract : Objective: To investigate the association between interleukin (IL)-1 α (rs1800587), IL-1 β (rs1143634) and IL-1 receptor antagonist (RN) variable number tandem repeat polymorphisms, expression levels and lumbar disc disease (LDD). Methods: All relevant articles were searched from 4 databases including PubMed, Embase, Web of Science and China National Knowledge Infrastructure. Odds ratios (OR) with 95% confidence intervals (CI) were calculated to evaluate the association between IL-1 gene locus polymorphisms (rs1800587 in IL-1 α, rs1143634 in IL-1 β, variable number tandem repeat in interleukin-1 receptor antagonist) and LDD susceptibility. Statistical analysis was conducted by Review Manager (Revman) 5.31 software (Nordic Cochrane Centre, Cochrane Collaboration, Copenhagen, Denmark). Furthermore, qRT-PCR and immunohistochemistry were performed to evaluate IL-1 α, IL-1 β and interleukin-1 receptor antagonist expressions in the normal and degenerated disc. Results: A total of 15 case-control studies (1455 cases and 2362 controls) were included in our meta-analysis. The pooled results suggested that IL-1 α rs1800587 polymorphism was associated with an increased risk of LDD in overall population (T vs. C, OR = 1.21, 95% CI = 1.04–1.40, P = .01). The subgroup analysis found a significant association between IL-1 β rs1143634 polymorphism and LDD in Asian population (T vs. C, OR = 0.61, 95% CI = 0.39–0.96, P = .03). Results of qRT-PCR and immunohistochemistry demonstrated that expressions of IL-1 α and IL-1 β were significantly increased in the degenerated disc. (all P < .05) Conclusion: IL-1 α rs1800587 and IL-1 β rs1143634 polymorphisms were significantly associated with LDD in overall population and in Asian population, respectively. The increased expression levels of IL-1 α and IL-1 β may be the important risk factors for LDD.